Penalaran Hukum: Bagaimana Merek Terkenal Diposisikan Melalui Positivisme Hukum - Adlhiyati, Zakki; Achmad, Achmad (Jurnal Ilmiah Kebijakan Hukum, 2023)
Legal protection for well-known mark needs to be examined. Indonesia has tried to conform its legal system with international law, most notably the Paris Convention and the TRIPS Agreement. However, the court’s decision indicates that the well-known mark remains unfavourable. This paper aimed to analyse judges’ rationale when they rejected a lawsuit against a well-known trademark in Indonesia which was the trademark dispute of “Starbucks” and Pierre “Cardin”. This study was conducted using legal research methods and it examined legal materials from judges’ decisions and literature review. Therefore, knowing the judge’s rationale for dismissing the claim is essential. In the first case, the plaintiff’s documented evidence was insufficient to establish the respondent’s bad faith, but the judge’s justification for rejecting the lawsuit was insufficient either. Meanwhile, in the second case, the judge denied the claim based on ne bis in idem, which aims to reach legal certainty, so the judge can lean more toward positivism. The positivism requires clear rules so as not to cause multiple interpretations. However, trademark and geographical indication law does not give complete regulations on well-known marks. As a result, problems and conflicts frequently arise in practice when it comes to the protection of well-known marks.